Effects of Mulligan Pain Release Phenomenon Technique in Management of Patellofemoral Pain Syndrome: RCT - Sahreen Anwar, Maham Javaid, Sarosh Malik, Muhammad Uzair Asghar, Wajida Perveen, Muqadas Chaudary (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Anterior knee pain is one of the common musculoskeletal problems seen in children adolescents and adults. Aim: To find the effects of Mulligan PRP technique in the management of patients with patellofemoral pain syndrome. Study design: Randomized Control Trial. Methodology: A randomized clinical trial was conducted with a sample of 45 patients. Equal no. of participants were allocated randomly in 3groups through computer generated random number table i.e. A (compression group), B (distraction group), C (conventional group) and allocation was kept concealed. Mulligan’s pain release phenomena with 3 different modifications were administered to the study groups. The duration of study was. Outcome measures were pain, knee range of motion, functional capability measured through Visual analogue scale (VAS), goniometer, and lower extremity functional scale (LEFS) respectively. Outcomes were measured at baseline and 4 weeks after the treatment. Data was analyzed by SPSS version 19. ANOVA was applied to find the outcomes while P ≤0.05 was considered significant. Results: The results of comparison among groups showed that knee ROM (P= 0.678), LEFS (P=0.027) and for VAS (P=0.163). The results showed that PRP is more effective in improving functional outcomes, whereas pain although improved through PRP; does not prove it a superior treatment when compared to others. Conclusion: We concluded that Mulligan’s Pain Release phenomena is an effective treatment in the management of patellofemoral pain syndrome in terms of functional outcomes.